Intermittent Calf Compression Delays the Onset of Presyncope in Young Healthy Individuals - Hockin, Brooke C. D.; Claydon, Victoria E. (Frontiers in Physiology, 2020)
Orthostatic fluid shifts reduce the effective circulating volume and thus contribute to syncope susceptibility. Recurrent syncope has a devastating impact on quality of life and is challenging to manage effectively. To blunt orthostatic fluid shifts, static calf compression garments are often prescribed to patients with syncope, but have questionable efficacy. Intermittent calf compression, which mimics the skeletal muscle pump to minimize pooling and filtration, holds promise for the management of syncope. We aimed to evaluate the effectiveness of intermittent calf compression for increasing orthostatic tolerance (OT; time to presyncope). We conducted a randomized single-blind crossover study, in which participants (n=21) underwent three graded, 60° head-up-tilt tests to presyncope with combined lower body negative pressure on separate days. Low frequency intermittent calf compression (ICLF; 4s on and 11s off) at 0-30mmHg and 0-60mmHg was applied during two tests and compared to a placebo condition where the garment was fitted, but no compression applied. We measured continuous leg circumference changes (strain gauge plethysmography), cardiovascular responses (finger plethysmography; Finometer Pro), end tidal gases (nasal cannula), and cerebral blood flow velocity (CBFv, transcranial Doppler). The 0-60mmHg ICLF increased OT (33±2.2min) compared to both placebo (26±2.4min; p<0.001) and 0-30mmHg ICLF (25±2.7min; p<0.001). Throughout testing 0-60mmHg ICLF reduced orthostatic fluid shifts compared to both placebo and 0-30mmHg ICLF (p<0.001), with an associated improvement in stroke volume (p<0.001), allowing blood pressure to be maintained at a reduced heart rate (p<0.001). In addition, CBFv was higher with 0-60mmHg ICLF than 0-30mmHg ICLF and placebo (p<0.001). Intermittent calf compression is a promising novel intervention for the management of orthostatic intolerance, which may provide affected individuals renewed independence and improved quality of life.